PERUBAHAN PENYAJIAN TALEMPONG GANDANG LASUANG DI NAGARI SIKAPAK TIMUR KOTA PARIAMAN - Tri Ananda; Marzam Marzam; Wimbrayardi Wimbrayardi (FBS Universitas Negeri Padang, 2018)
Abstract Talempong Gandang Lasuang is a traditional art in Nagari Sikapak Timur, Kota Pariaman. It is used as an entertainment in cooking activities in the kitchen to prepare for the Baralek (wedding ceremony). Nowadays, Talempong Gandang Lasuang art is no longer played in the kitchen, but it has become an art performance. In line, there are several changes in the presentation of Talempong Gandang Lasuang. These changes are seen from several aspects, including changes in the place of performance, instrument changes, and changes in musical form. This article was prepared based on the Thesis titled